Analisis Tentang Sistem Penyelesaian Sengketa WTO : Suatu Tinjauan Yuridis Formal (Lex Jurnalica, 2014)
AbstractThis study applied normative legal research method, with literature approach on how the norms in WTO Agreement. Analysis applied in this study is descriptice-analyses approach. The main issue here is on how the special arrangement applied on the settlement of dispute system under WTO may be beneficial to developing countries and what is the ideal special arrangement on settlement of dispute system under WTO for Indonesia, and how it may benefit the interest of Indonesia. Objective of the study is to understand how the settlement mechanism under WTO can be beneficial for developing countries and in particular, what is the ideal special arrangement on settlement of dispute under WTO for Indonesia, and its benefit to the national interest of Indonesia. The conclusion of the study shows that there are special arrangements on procedures of settlement of dispute applied by the WTO’s Dispute Settlement Body as refinement of the GATT 1947 mechanism, with the ratification of the Understanding On Rules and Procedures Governing The Settlement of Disputes, and this becomes part of requirement packages which must be followed and adhered to by all members of WTO without exception. However, on the other side, with some of identified weakness of DSU, it is expected that developing countries, particularly Indonesia, shall be able to get the benefit of it for our national interest. Indonesia has indeed used the system to support its own interest. Based on some case studies where Indonesia had to seek settlement in the forum of dispute of WTO, it is expected that there will be refinement of on the DSU mechanism, inter alia, shorter time in each stages of settlement process, arrangement of DSB resolution implementation to make it more effective, special arrangement to prevent retaliation mechanism in DSU, and special arrangement needed to increase the role of WTO Secretariat in the support of dispute settlement case which involve advanced countries versus developing countries and the need to have special arrangement to increase the function and role of DSB on each stages of dispute settlement process (especially in the DSB recommendation to be implemented as provided here).Keywords: WTO, DSB, international trade disputeAbstrakPenelitian ini menggunakan metode penelitian hukum normatif, dengan melakukan studi pustaka terhadap berbagai norma dan kaidah hukum yang terdapat dalam WTO Agreement dan dianalisis dengan deskriptif-analitis. Yang menjadi permasalahan bagaimanakah pengaturan khusus mengenai sistem penyelesaian sengketa WTO yang bermanfaat bagi negara-negara berkembang dan bagaimanakah seharusnya pengaturan khusus mengenai sistem penyelesaian sengketa WTO dan manfaatnya bagi kepentingan nasional Indonesia. Tujuan penelitian ini adalah untuk mengetahui pengaturan khusus mengenai sistem penyelesaian sengketa WTO yang bermanfaat bagi negara-negara berkembang dan untuk mengetahui pengaturan khusus yang seharusnya mengenai sistem penyelesaian sengketa WTO dan manfaatnya bagi kepentingan nasional Indonesia. Kesimpulan hasil penelitian bahwa terdapat ketentuan khusus yang berlaku mengenai prosedur penyelesaian sengketa yang diterapkan oleh Dispute Settlement Body yang telah disempurnakan dari sistem GATT 1947 dengan disahkannya Understanding On Rules and Procedures Governing The Settlement of Disputes dan merupakan satu paket ketentuan yang wajib ditaati dan diikuti serta dilaksanakan bagi para anggota WTO dan setiap keputusannya wajib diikuti tanpa terkecuali. Adapun diharapkan adanya penyempurnaan pengaturan dalam DSU antara lain waktu yang Analisis Tentang Sistem Penyelesaian Sengketa WTO : Suatu Tinjauan Yuridis Formal Lex Jurnalica Volume 11 Nomor 2, Agustus 2014 156 lebih singkat dalam tiap tahapan dalam sistem penyelesaian sengketa WTO, pengaturan pelaksanaan putusan DSB agar lebih efektif, perlunya pengaturan khusus mengenai mekanisme retaliasi dalam DSU, perlunya pengaturan khusus dalam rangka meningkatkan peran WTO Secretariat dalam membantu menyelesaian sengketa yang menghadapkan antara negara maju dan negara berkembang dan perlunya pengaturan khusus dalam meningkatkan fungsi dan peranan DSB pada setiap tahapan proses penyelesaian sengketa (terutama dalam pelaksanaan rekomendasi DSB yang diberikan).Kata kunci: WTO, DSB, sengketa dagang internasional